PERENCANAAN STRATEGIS PENGEMBANGAN MINAPOLITAN (Studi di Desa Kemangi, Kecamatan Bungah, Kabupaten Gresik) - Adhinda Dewi Agustine (Universitas Merdeka Malang, 2017)
Based on the Decree of the Minister of Marine Affairs and Fisheries No. 35 of 2013 on the Determination of Minapolitan Areas, Gresik Regency includes the Minapolitan area. The fishery cultivation sector of Gresik Regency has the potential to be optimized. This is supported by the sea area of Gresik Regency covering 22% of the total area (Gresik Dalam Dalam 2015). But the problem of synergy between institutions or related agencies that play a role in running this Minapolitan Area is still not optimal. And fish farmers as subjects and objects in Minapolitan concept, have their own mindset that does not match the direction given by the Related Office.DOI: https://doi.org/10.26905/pjiap.v2i1.1420